'They aren't really black fellas but they are easy to talk to': Factors which influence Australian Aboriginal women's decision to disclose intimate partner violence during pregnancy. (October 2016) - Spangaro, Jo; Herring, Sigrid; Koziol-Mclain, Jane; Rutherford, Alison; Frail, Mary-Anne; Zwi, Anthony B.
Abstract: Objectives: intimate partner violence is a significant global health problem but remains largely hidden. Understanding decisions about whether or not to disclose violence in response to routine enquiry in health settings can inform safe and responsive systems. Elevated rates of violence and systematic disadvantage found among Indigenous women globally, can impact on their decisions to disclose violence. This study aimed to test, among Indigenous women, a model for decisions on whether to disclose intimate partner violence in the context of antenatal routine screening. Design: we employed Qualitative Configurative Analysis, a method developed for the social sciences to study complex phenomena with intermediate sample sizes. Data were drawn from single semi- structured interviews with Indigenous women 28+ weeks pregnant attending antenatal care. Interviews addressed decisions to disclose recent intimate partner violence in the context of routine enquiry during the antenatal care. Interview transcripts were binary coded for conditions identified a priori from the model being tested and also from themes identified within the current study and analysed using Qualitative Configurative Analysis to determine causal conditions for the outcome of disclosure or non-disclosure of violence experienced. Settings: five Aboriginal and Maternal Infant Health Services (two urban and three regional), and one mainstream hospital, in New South Wales, Australia. Participants: indigenous women who had experienced partner violence in the previous year and who had been asked about this as part of an antenatal booking-in visit. Of the 12 participants six had elected to disclose their experience of violence to the midwife, and six had chosen not to do so. Findings: pathways to disclosure and non-disclosure were mapped using Qualitative Configurative Analysis. Conditions relevant to decisions to disclose were similar to the conditions for non-Aboriginal women found in our earlier study. Unique to Aboriginal women's decisions to disclose abuse was cultural safety. Cultural safety included elements we titled: Borrowed trust, Build the relationship first, Come at it slowly and People like me are here . The absence of cultural safety Its absence was also a factor in decisions not to disclose experiences of violence by this group of women. Key conclusions: cultural safety was central to Indigenous women's decision to disclose violence and processes for creating safety are identified. Other forms of safety which influenced disclosure included: safety from detection by the abuser; safety from shame; and safety from institutional control. Disclosure was promoted by direct asking by the midwife and a perception of care. Non-disclosure was associated with a lack of care and a lack of all four types of safety. Experiences of institutional racism were associated with Indigenous women's perceived risk of control by others, particularly child protection services. Implications for practice: policies to ask abuse questions at first visits and models where continuity of care is not maintained, are problematic for Aboriginal women, among whom relationship building is important as is ample warning about questions to be asked. Strategies are needed to build cultural safety to counter widespread racism and promote safe opportunities for Indigenous women to disclose intimate partner violence and receive support. Elements of cultural safety are necessary for vulnerable or marginalised populations to fully utilise available health services. Highlights: Globally Indigenous women experience higher levels of intimate partner violence. Disclosure of partner abuse was mapped using Qualitative Configurative Analysis. Cultural safety was critical to Aboriginal women's decisions to disclose their abuse. Fears of child protection intervention disrupts Aboriginal women's engagement with antenatal care. Experiences of institutional racism when using mainstream services were common for Aboriginal women in this study.